Kilka uwag o subkompetencji frazeologicznej tłumacza - Szutkowski, Tomasz (Acta Polono-Ruthenica, 2019)
The topic of this article is a diagnosis of the level of a phraseological sub-competence of a translator conducted on the basis of a survey carried out among students of neophilology with the translator specialization. The aim of the study is to determine the level of linguistic awareness of the surveyed in the area of phraseological sub-competence. The question posed is in what way they comprehend the essence of the multi-word linguistic units and if they can extract supra-lexical units of a translation. As such, the accuracy of a translation is dependent on the correct segmentation of the original. Those surveyed, faced with a 99-word text containing 25 multi-word linguistic units (75% of the whole text), extracted only seven of such structures in at least 50% of their answers. It can be deduced that the students consider phraseological units extremely idiomatic. In most cases, they do not notice other, less prototypical structures in the text, which should be considered globally in the process of translation. This conclusion justifies the undertaking of firm action in the area of phraseodidactics and phrasal translation as part of a philological academic education.